Teacher candidates' perspectives on inclusive education: A case study of mentored inclusive research - Sarah M. Hart (Journal of Pedagogical Research, 2024)
Pre-service teachers desire an innovative and inclusive future for education yet feel underprepared to realistically transform their future classrooms. In this study, teacher candidates were mentored in inclusive research that captured the perspectives of young adults with significant disabilities during their post-school transitions. Following these experiences, those preparing to become teachers in the US reflected on their research participation. Described in this paper are their influences, ideas, and possible implementation strategies, in particular, during the highly unstable times of the pandemic and associated lockdowns. Two key themes of resilience and complexity were considered pivotal to converting research experiences into future inclusive classroom practices. Additional teacher education strategies support future educators with an open and exploratory approach that conveys deep respect for the educational field.